Membrane concentrate treatment by photosynthetic bacteria: Feasibility and tolerance mechanism analysis. (April 2018) - Yang, Anqi; Zhang, Guangming; Meng, Fan; Zhang, Panyue; Chen, Yang
Graphical abstract: Highlights: PSB simultaneously removed COD, NH3 -N, NO3 -N, salinity and chroma from concentrate. Dark-aerobic condition was more beneficial for pollutant removal. The contents of protein and carotenoid increased due to defense stress effect. As common electron-transfer mediator in PSB, coenzyme Q10 's content was stable. Abstract: Refractory membrane concentrate generated from the membrane bioreactor (MBR) process remains a big challenge. With high pollution loads, high salinity and low biodegradability, membrane concentrates are difficult to be treated by conventional biological treatments. In this work, photosynthetic bacteria (PSB) were employed to handle this problem. The results showed that PSB could simultaneously remove COD, NH3 -N, NO3 − -N, salinity and chroma from the membrane concentrate. The removal efficiency of COD, NH3 -N, NO3 − -N, salinity and chroma reached 24.0%, 78.0%, 81.6%, 57.0% and 60.0% respectively. Dark-aerobic condition was more beneficial for pollutants removal. The tolerance mechanism of PSB in treating membrane concentrate was then analyzed. The contents of protein and carotenoid in PSB increased by 38.7% and 20.7% due to the defense stress effects. The content of bacteriochlorin decreased by 42.9% while the content of coenzyme Q10 was stable at 8.4–8.8%.